Teladan Moral dalam Alkitab: Pendidikan Karakter dari Kehidupan Tokoh Alkitab - Sinambela, Juita; Sinaga, Janes; Hutabarat, Bernard Maruli; Woran, Ramlen; Siswanto, Daniel (Global Education Journal, 2023)
The aims of this study are to: Analyze the character values that can be learned from the stories of Bible characters. Character education has become a major concern in the world of modern education. Along with technological developments and globalization, moral and ethical challenges are increasingly complex, thus giving an urgency to prioritize character education among the younger generation. Character must be continuously formed to make someone with a strong character. Losing character, that means we have lost everything. Thus expressing how important character is in this life. This research will use a qualitative approach through literature studies involving analysis of Bible texts, textbooks on character education, as well as research related to religious and moral education. This research makes a significant contribution to the world of education, especially in developing strategies and character education programs that are more holistic and based on solid moral values. By understanding and applying the moral examples of Bible characters, it is hoped that this will create a generation with strong character and the potential to become leaders with integrity in the future.